2020
DOI: 10.1212/wnl.0000000000010647
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in incidence, comorbidity, and mortality of ischemic stroke in Denmark (1996–2016)

Abstract: ObjectiveTo examine whether the incidence, comorbidity, and mortality of first-time ischemic stroke changed in Denmark between 1996 and 2016 overall and according to age and sex using a nationwide cohort design.MethodsIn this cohort study, 224,617 individuals ≥18 years admitted with first-time ischemic stroke between 1996 and 2016 were identified using Danish nationwide registries. We calculated annual age-standardized incidence rates and absolute 30-day and 1-year mortality risks. Further, we calculated annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
5
19
2
2
Order By: Relevance
“…We observed that tendency of comorbidity increasing and aging populations was in line with the study in a developed country of Denmark 8,9 . While a more serious aging trend in Denmark was observed with the predominance of rst-stroke people aged ≥ 70 years (almost 63%), and patients aged 65 years old was the dominant for those with ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that tendency of comorbidity increasing and aging populations was in line with the study in a developed country of Denmark 8,9 . While a more serious aging trend in Denmark was observed with the predominance of rst-stroke people aged ≥ 70 years (almost 63%), and patients aged 65 years old was the dominant for those with ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that tendency of comorbidity increasing and aging populations was in line with the study in a developed country of Denmark [ 9 , 10 ]. While a more serious aging trend in Denmark was observed with the predominance of first-stroke people aged ≥ 70 years (almost 63%), and patients aged 65 years old was the dominant for those with ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…Alongside this, the hazard factors of stroke also affect prevalence of many chronic diseases (e.g., myocardial infarction, diabetes, chronic obstructive pulmonary disease, and cancer). Previous studies conducted in developed countries illustrated comorbidity is a strong factor affecting short- and long-term mortality of post-stroke [ 9 , 10 ], as well as economic burden in admission [ 11 ]. However, few studies are devoted to the relationship between stroke and comorbidity in the condition of an aging population with increasing prevalence of comorbidity in China.…”
Section: Introductionmentioning
confidence: 99%
“…A study of time trends in Demark found that first‐time hospitalization for ischemic stroke increased from 1996 to 2002 and then gradually decreased to below the initial level until 2016 29 . In the current study, we found that there were 89 077 unweighted cases of stroke in 2006 which increased to 113 749 in 2014.…”
Section: Discussionsupporting
confidence: 50%